116k views
3 votes
Does anybody know this????

Does anybody know this????-example-1
User Ben Groot
by
5.6k points

1 Answer

0 votes

Answer:

(f - g)(x) = -x² + 3x + 7 ⇒ D

Explanation:

In the expression x - a, you will subtract a from x

Let us solve the question using this fact

f(x) = 3x + 1

g(x) = x² - 6

→ We need to find (f - g)(x), which means subtract g from x

∵ (f - g)(x) = (3x + 1) - (x² - 6)

→ The negative sign before (x² - 6) will change their signs

∵ - (x² - 6) = -(x²) + -(-6)

→ Remember (-)(+) = - and (-)(-) = (+)

- (x² - 6) = -x² + 6

→ Substitute it in (f - g)(x)

∴ (f - g)(x) = 3x + 1 - x² + 6

→ Add the like terms

∴ (f - g)(x) = 3x - x² + (1 + 6)

∴ (f - g)(x) = 3x - x² + 7

→ Re-arrange the terms from the greatest power of x

(f - g)(x) = -x² + 3x + 7

User Xmarston
by
5.4k points